LEGAL FOUNDATION OF DETERMINING CRITERIA OF IMPROPER RENDERING OF MEDICAL AID IN RUSSIAN FEDERATION - N. Balashova, Tatyana; A. Chernysheva, Yuliya (Gênero & Direito, 2020)
This scientific paper is aimed at reviewing the applicable laws governing the medical aid rendering to the Russian Federation citizens, in particular, the RF Civil Code, the Federal Law dated 21.11.2011 No. 323-FZ “On fundamental healthcare principles in the Russian Federation”, the RF Law dated 07.07.1992 No. 2300-1 “On Protection of Consumers’ Rights”, and a number of subordinate regulatory legal acts. The article’s authors tried to analyze and to reveal criteria of improper rendering of medical aid in the Russian Federation. The authors substantiated that the medical aid, as a complex of measures, which are aimed at maintaining and (or) recovering the health and which include the rendering of medical services, must correspond to the criteria of a proper quality, a proper volume, it must be rendered by highly-qualified specialists properly, at the appropriate time and with complying with the established rights of the patients, and a notion of improper medical aid is defined. A general scientific dialectical method and a complex of scientific approaches of obtaining knowledge (formally-legal, system-structural, formally-logical) is the research’s methodological framework. The results, which the authors obtained, consist in the fact that as criteria of improper rendering of the medical aid, it is necessary to consider the conditions, volume, safety, quality, non-conformity of the medical aid with the goals, for which this medical aid is usually rendered, violation of the patients’ rights, non-optimal choice of a technology of the medical aid rendering, violation of the rights of execution of the medical documentation. In the conclusion the authors formulated the basic conclusions of the research, substantiated the necessity to develop and to enshrine an enumeration of criteria of the improper rendering of the medical aid in the applicable laws.